2022
DOI: 10.1126/sciimmunol.abl9925
|View full text |Cite
|
Sign up to set email alerts
|

CD103 fate mapping reveals that intestinal CD103 tissue-resident memory T cells are the primary responders to secondary infection

Abstract: Tissue-resident memory T (T RM ) cells remain poised in the tissue and mediate robust protection from secondary infection. T RM cells within the intestine and other tissues are heterogeneous in their phenotype and function; however, the contributions of these T RM subsets to secondary infection remain poorly defined. To address the plasticity of intestinal T RM subsets and their role in local and systemic immunity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 69 publications
(106 reference statements)
1
28
0
Order By: Relevance
“…CD8 + TRM cells within a variety of tissue compartments are heterogeneous in phenotype and function, and can be broadly divided into two subpopulations based on CD103 expression: CD69 + CD103 -CD8 + TRM (CD103n CD8 + TRM) and CD69 + CD103 + CD8 + TRM (CD103p CD8 + TRM) cells (11). Some tissues, such as intestinal and salivary gland, harbor both CD103p and CD103n CD8 + TRM subsets, and these two populations displayed distinct functional capabilities in the context of response to infection (12)(13)(14). However, the characteristics differences of these TRM subsets and their contributions in pSS remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…CD8 + TRM cells within a variety of tissue compartments are heterogeneous in phenotype and function, and can be broadly divided into two subpopulations based on CD103 expression: CD69 + CD103 -CD8 + TRM (CD103n CD8 + TRM) and CD69 + CD103 + CD8 + TRM (CD103p CD8 + TRM) cells (11). Some tissues, such as intestinal and salivary gland, harbor both CD103p and CD103n CD8 + TRM subsets, and these two populations displayed distinct functional capabilities in the context of response to infection (12)(13)(14). However, the characteristics differences of these TRM subsets and their contributions in pSS remain poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…and Fung et al. showed that CD103 + T RM cells have limited proliferation capacity, but CD103 - T RM cells undergo robust expansion upon Ag re-encounter, further highlighting the heterogeneity within T RM pool ( 121 , 122 ). Nonetheless, successive Ag exposures improve the longevity and protective function of T RM pool; for example, 4° influenza-specific T RM cells show enhanced durability and heterosubtypic immunity than 1° T RM cells ( 123 ).…”
Section: Evolution Of the T Mem Pool After Multipl...mentioning
confidence: 99%
“…A set of recent mouse model studies used elegant fate-mapping approaches to assess how intestinal T RM respond to TCR-mediated reactivation. 84,85 These CD8 T-cell-focused studies found that CD103+ T RM cells had fairly limited responses to TCRmediated reactivation. We hypothesize that a similar level of T RM hyporesponsiveness may exist in the FRT, helping to maintain T RM homeostasis during inflammatory episodes.…”
Section: Maintaining Homeos Ta S Is -The T R M Compartment In Infl Am...mentioning
confidence: 99%
“…Of note, this baseline level of inflammation appears to be critical for maintenance of barrier immunity (“inflammatory surveillance”). A set of recent mouse model studies used elegant fate‐mapping approaches to assess how intestinal T RM respond to TCR‐mediated reactivation 84,85 . These CD8 T‐cell‐focused studies found that CD103+ T RM cells had fairly limited responses to TCR‐mediated reactivation.…”
Section: Maintaining Homeostasis—the Trm Compartment In Inflamed Tissuesmentioning
confidence: 99%